Vibration analysis of cross-ply laminated composite doubly curved shallow shell panels with stiffeners - Tuan, Trinh Anh; Tu, Tran Minh; Quoc, Tran Huu; Loi, Nguyen Van (Vietnam Journal of Science and Technology, 2017)
In this paper, the analytical solution for the cross-ply laminated composite double curved shell panels with stiffeners is presented. Based on the smeared stiffeners technique and the first shear deformation theory (FSDT), the motion equations are derived by applying the Hamilton’s principle. The Navier’s solution for the simply supported boundary condition for all edges is presented. The numerical results are veriﬁed with the known results in the literature. The effects of the number of stiffeners, dimensions of stiffeners, and lamination scheme of cross-ply laminated composite doubly curved shell panels on the natural fundamental frequencies are investigated.